PENGARUH MOTIVASI DAN MODAL USAHA TERHADAP MINAT BERWIRAUSAHA DI PASAR KOMPLEK MMTC KOTA MEDAN - Nalom Siagian; Darma Manalu (LPPM Universitas HKBP Nommensen, 2021)
This study aims to determine the effect of motivation and working capital on interest in entrepreneurship through research with a quantitative approach. The object of the research is entrepreneurs in the MMTC Complex Market, Medan City, totaling 100 entrepreneurs, using primary and secondary data through a liskert scale questionnaire. The research data was processed through validity testing, reliability testing, multiple regression and hypothesis testing through partial and simultaneous tests.Based on the results of the validity and reliability tests, the variables Motivation (X₁), Business capital (X₂) and Entrepreneurial Interest (Y) can be concluded as valid and reliable based on the test criteria rcount rtable and combrach alpha 0.6 of all indicators of each variable . Based on the ttable test criteria, the calculated t value for the Motivation variable (X₁) = 6.264 > t table (α = 0.05/2; n-k-1) = 1.985. It means that the motivation variable (X₁) has a positive effect on entrepreneurial interest. Based on the t-table test criteria, the calculated t-value generated on the variable Business Capital (X₂) = -0.288 < t table (α = 0.05/2; n-k-1) = 1.985. This means that the working capital variable (X₂) has a negative effect on entrepreneurial interest. Based on Table 4.18, the calculated F value is 20.802 > F table (α = k; n-k) = 2.70 with F sig. 0.000 where F sig. 0.000 < 0.05 then H0 is rejected. It can be interpreted that motivation (X₁) and working capital (X₂) have a positive and significant effect simultaneously on interest in entrepreneurship (Y).